Pengaruh Dukungan Sosial Terhadap Keputusan Karir pada Mahasiswa Universitas Pamulang - Nova Nurannisa; Erikha Shara Putri Sagita (Universitas 45 Surabaya, 2025)
This research aims to analyze the influence of social support on career decisions among Pamulang University students. The social support in question includes support from family, friends and the academic environment. The method used in this research is a quantitative survey involving 200 student respondents. Data was collected using a questionnaire and analyzed using linear regression techniques. The research results show that social support has a significant positive influence on students' career decisions. These results imply that the higher the social support students receive, the better the career decisions they make. This research provides recommendations for educational institutions to strengthen social support networks in helping students plan and make the right career decisions.